Health-seeking behavior among non-communicable disease patients globally, systematic review and meta-analysis - Tadele Fentabil Anagaw; Elyas Melaku Mazengia; Eyob Ketema Bogale; Eneyew Talie Fenta; Habitu Birhan Eshetu; Natnael Kebede; Sintayehu Shiferaw Gelaw; Amare Zewdie; Tadele Derbew Kassie (SAGE Open Medicine, 2023)
Introduction: Non-communicable disease contributes to over 42 million deaths worldwide and it is estimated that 86% of non-communicable disease-related mortalities happen in low and middle-income countries. Understanding health-seeking behaviors like initiating care at the right time, with the right provider and maintaining regularity of care seeking is a prelude for a successful management of non-communicable diseases. Therefore, the aim of this systematic review and meta-analysis was to assess the pooled prevalence of health-seeking behavior for non-communicable disease and associated factors worldwide. Method: Preferred Reporting Items for Systematic Reviews and Meta-Analysis checklist guideline was followed for this review and meta-analysis. Electronic data base, PubMed, EMBASE, Medline, Web of science, Google scholar and Science direct were used to retrieve studies reported in English language with publication year since 2018 worldwide. Studies reporting proportion of health-seeking behavior for non-communicable disease were evaluated. The pooled prevalence, odds ratio and confidence interval were calculated using Stata version 17 software. The quality of studies included in this review was checked using modified Newcastle-Ottawa scale for observational study checklist. Result: Ten studies which involved 63,498 patients with non-communicable disease were included in this review. The pooled estimated proportion of health-seeking behavior among non-communicable diseases patients from health facilities were 56% (95% CI: 44–68). Older age > 60, urban residency, being of female gender, high educational status, getting support during treatment, knowledge on non-communicable disease, having more than one non-communicable disease, presences of health insurance and middle and upper economic class were factors positively associated with health-seeking behavior for non-communicable diseases. Conclusion: Despite the fact that more than half of patients with non-communicable diseases have health-seeking behavior in health facilities, still, there are a considerable number of individuals with non-communicable diseases having no health-seeking behavior worldwide. Therefore, organizations working for the welfare of human betterment would do well in implementing strategies that could improve health-seeking behavior that would help to reduce the burdens on health systems and prevent premature death from non-communicable diseases.